Effects of coloring procedures on zirconia/veneer ceramics bond strength. - Tuncel, İlkin; Özat, Pelin; Eroğlu, Erdal (My University, 2014)
The most common failure seen in restorations with a zirconia core is total or layered delamination of the ceramic veneer. In the present study, the shear bond strengths between veneering ceramics and colored zirconia oxide core materials were evaluated.

Zirconia discs (15 × 12 × 1.6 mm) were divided into 11 groups of 12 discs each. Groups were colored according to the Vita Classic scale: A3, B1, C4, D2, and D4. Each group was treated with the recommended shading time for 3 s, or with prolonged shading for 60 s, except for the control group. Samples were veneered with 3 mm thick and 3.5 mm in diameter translucent ceramic and subjected to shear test in a universal testing machine with a crosshead speed of 1 mm/min. One-way analysis of variance (ANOVA) and Tukey's HSD tests were used for comparisons of the groups having the same shading times. A paired t-test was used for groups of the same color (3 s/60 s).

Among the 11 groups investigated C4 (3 s) had the highest bond strength with a value of 36.40 MPa, while A3 (3 s) showed the lowest bond strength with a value of 29.47 MPa.

Coloring procedures can affect zirconia/ceramic bond strength. However, the results also showed that bond strengths of all the investigated groups were clinically acceptable.
Keywords: Bond strength; Coloring pigments; Veneering ceramic; Zirconia